Siwa–Buddha sebagai Strategi Transformasi Keagamaan: Membaca Bukti Material dan Tekstual pada Masa Bali Kuno - Heri Purwanto; Ni Kadek Surpi; Made Ayu Diah Indira Virgiastuti; Ni Wayan Jemiwi Jero (Humanis, 2025)
This article examines Shiva-Buddha as a strategy for religious transformation rather than syncretism or fusion by linking material evidence (architecture, iconography, sacred spatial arrangements) with textual evidence (inscriptions and kakawin). The database includes traces from East Java and Ancient Bali, such as the Kelurak Inscription (782 AD), the Gajah Mada Inscription (1291 AD), the Kakawin Nāgarakṛtāgama, and a corpus of Balinese inscriptions mentioning śaiwasogata, balanced by readings of the sites of Singasari, Jawi, Kidal, Jago, Jabung, Surawana, Gunung Kawi, Goa Gajah, and the Tirta Empul and Pegulingan complexes. The methodology combines epigraphic criticism, architectural-iconographic typological analysis, and textual hermeneutics. The main findings are (1) a consistent two-layer pattern, transformation bound within the material realm (Shiva and Buddha are present, but still follow their respective rules) and free transformation in the realm of devotion, which brings them together without forming a new religion; (2) a politico-ritual function as a technology of legitimation as well as a mechanism of social integration; (3) two main drivers, local innovative power and the tantrayana medium that provides cross-traditional cosmology, icons, and rituals.